2020
DOI: 10.5130/ccs.v12.i1.6872
|View full text |Cite
|
Sign up to set email alerts
|

„Multi-culti“ vs. ”another cell phone store“ – Changing ethnic, social, and commercial diversities in Berlin-Neukölln.

Abstract: Based on an extensive ethnography of the economic and social life in Berlin-Neukölln, the paper asks how a changing demographic and social structure affects the social life but also the urban renewal on two iconic but contested streets - “the Arab street” Sonnenallee and adjacent Karl-Marx-Straße. The effects of migration - and particularly of the more recent refugee migration - to Berlin are explored through the reshaping and diversification processes of the physical and social spaces of the two stree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The Arab district-mainly called the "the Arab street" (Sonnenallee)-in Berlin shows the effects of migration, and particularly of the more recent refugee migration after the war in Syria. This area has been changed due to reshaping and diversification processes of the physical and social spaces of the street and is now mainly dominated by Syrians (Steigemann, 2020). Participants primarily explain that the reason for not abiding by the preventive measures in this street is religion.…”
Section: Avoidance Of An Arab Neighbourhood In Berlinmentioning
confidence: 99%
See 1 more Smart Citation
“…The Arab district-mainly called the "the Arab street" (Sonnenallee)-in Berlin shows the effects of migration, and particularly of the more recent refugee migration after the war in Syria. This area has been changed due to reshaping and diversification processes of the physical and social spaces of the street and is now mainly dominated by Syrians (Steigemann, 2020). Participants primarily explain that the reason for not abiding by the preventive measures in this street is religion.…”
Section: Avoidance Of An Arab Neighbourhood In Berlinmentioning
confidence: 99%
“…Apart from its physical effects, the COVID-19 pandemic has had several kinds of psychological and social impacts ( Takieddine & Al Tabbah, 2020 ). A study in China that aimed to investigate if psychiatric patients experience more symptoms during the COVID-19 pandemic showed that the levels of anxiety, depression, and stress were higher in psychiatric patients than in healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…Inclusions and exclusions of migration in the process of neighbourhood change -Upgrading processes of disadvantaged inner-city areas with a high proportion of 'ethnic minorities' and infrastructures for immigrants have already been frequently documented and analysed in urban research (Zukin 2008;Murdie & Teixeira 2011;Tissot 2015). Particularly relevant is research that has focused on immigrants' agency by studying the role of ethnic enterprises in the process of economic, functional and symbolic upgrading (Aytar & Rath 2012;Steigemann 2020). In this context, a neoliberal lens has often been criticised, viewing the ethnic and cultural diversity of actors primarily in terms of their positive influence on innovation and economic growth, but largely ignores existing exclusion and disadvantages in everyday life (Zukin 2008;Leslie & Catungal 2012;Martin 2014;van Eck et al 2020).…”
Section: Introductionmentioning
confidence: 99%